miRNA Signatures in Alveolar Macrophages Related to Cigarette Smoke: Assessment and Bioinformatics Analysis - Mirra, Davida; Esposito, Renata; Spaziano, Giuseppe; Rafaniello, Concetta; Panico, Francesca; Squillante, Antonio; Falciani, Maddalena; Abrego-Guandique, Diana Marisol; Caiazzo, Eleonora; Gallelli, Luca; Cione, Erika; D’Agostino, Bruno (International journal of molecular sciences, 2025)
Cigarette smoke (CS) is a driver of many respiratory diseases, including chronic obstructive pulmonary disease (COPD) and non-small cell lung cancer (NSCLC). Tobacco causes oxidative stress, impaired phagocytosis of alveolar macrophages (AMs), and alterations in gene expression in the lungs of smokers. MicroRNAs (miRNAs) are small non-coding RNAs that influence several regulatory pathways. Previously, we monitored the expressions of hsa-miR-223-5p, 16-5p, 20a-5p, -17-5p, 34a-5p, and 106a-5p in AMs derived from the bronchoalveolar lavage (BAL) of subjects with NSCLC, COPD, and smoker and non-smoker control groups. Here, we investigated the capability of CS conditionate media to modulate the abovementioned miRNAs in primary AMs obtained in the same 43 sex-matched subjects. The expressions of has-miR-34a-5p, 17-5p, 16-5p, 106a-5p, 223-5p, and 20a-5p were assessed before and after in vitro CS exposure by RT-PCR. In addition, a comprehensive bioinformatic analysis of miRNAs KEGGS and PPI linked to inflammation was performed. Distinct and common miRNA expression profiles were identified in response to CS, suggesting their possible role in smoking-related diseases. It is worth noting that, following exposure to CS, the expression levels of hsa-miR-34a-5p and 17-5p in both smokers and non-smokers, 106a-5p in non-smokers, and 20a-5p in smokers, shifted towards those found in individuals with COPD, suggesting them as a risk factor in developing this lung condition. Moreover, CS-focused sub-analysis identified miRNA which exhibited CS-dependent pattern and modulated mRNA involved in the immune system or AMs property regulation. In conclusion, our study uncovered miRNA signatures in AMs exposed to CS, indicating that CS might modify epigenetic patterns that contribute to macrophage activation and lung disease onset and progression.